Origin of Mercury’s double magnetopause: 3D hybrid simulation study with A.I.K.E.F. - Müller, J.; Simon, S.; Wang, Y.-C.; Motschmann, U.; Heyner, D.; Schüle, J.; Ip, W.-H.; Kleindienst, G.; Pringle, G. J. (Icarus, 2012)
During the first and second Mercury flyby the MESSENGER spacecraft detected a dawn side double-current sheet inside the Hermean magnetosphere that was labeled the “double magnetopause” (Slavin, J.A. et al. [2008]. Science 321, 85). This double current sheet confines a region of decreased magnetic field that is referred to as Mercury’s “dayside boundary layer” (Anderson, M., Slavin, J., Horth, H. [2011]. Planet. Space Sci.). Up to the present day the double current sheet, the boundary layer and the key processes leading to their formation are not well understood. In order to advance the understanding of this region we have carried out self-consistent plasma simulations of the Hermean magnetosphere by means of the hybrid simulation code A.I.K.E.F. (Müller, J., Simon, S., Motschmann, U., Schüle, J., Glassmeier, K., Pringle, G.J. [2011]. Comput. Phys. Commun. 182, 946–966). Magnetic field and plasma results are in excellent agreement with the MESSENGER observations. In contrast to former speculations our results prove this double current sheet may exist in a pure solar wind hydrogen plasma, i.e. in the absence of any exospheric ions like sodium. Both currents are similar in orientation but the outer is stronger in intensity. While the outer current sheet can be considered the “classical” magnetopause, the inner current sheet between the magnetopause and Mercury’s surface reveals to be sustained by a diamagnetic current that originates from proton pressure gradients at Mercury’s inner magnetosphere. The pressure gradients in turn exist due to protons that are trapped on closed magnetic field lines and mirrored between north and south pole. Both, the dayside and nightside diamagnetic decreases that have been observed during the MESSENGER mission show to be direct consequences of this diamagnetic current that we label Mercury’s “boundary-layer-current“.